PENGARUH TRANSPARANSI KEUANGAN, ETIKA MANAJERIAL, DAN PERHITUNGAN BIAYA PRODUKSI TERHADAP PELAKU UMKM DI DAERAH CIKARANG - Ayu Ertina; Muhammad Kosim; Dede Sunarti; Alfira Lida Aenuh Hikmah; Febriansyah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore in depth how financial transparency, the application of managerial ethics, and the accuracy of production cost calculations influence business practices among Micro, Small, and Medium Enterprises (MSMEs). Using a descriptive qualitative approach, data were collected through open-ended interviews, direct field observations, and analysis of relevant documents. The findings indicate that a lack of financial transparency hinders effective decision-making. On the other hand, the consistent application of ethical managerial principles significantly contributes to fostering harmonious relationships with stakeholders. Inaccurate cost calculations also lead to improper pricing strategies and decreased operational efficiency. These three elements are interrelated and collectively contribute to building a professional and sustainable business management system. The study highlights the importance of strengthening MSME managerial capacity through collaboration among government institutions, business actors, and support organizations, particularly in the areas of financial literacy, ethical business conduct, and cost efficiency.